Answer:
see below
Step-by-step explanation:
We can just add up all of these fractions:
2 1/8 + 7/8 = 2 8/8 = 3
8 5/8 + 4/8 = 8 9/8 = 9 1/8
3 + 9 1/8 = ![12\frac{1}{8}](https://tex.z-dn.net/?f=12%5Cfrac%7B1%7D%7B8%7D)
Answer:
36" / 2.25" * 14 = 16 * 14" = 224 inches =
18.666666 feet = 18 feet 8 inches
Step-by-step explanation:
Answer:
C - The failure was a starting point for a buildup of aggression around the world.
Step-by-step explanation:
EDGE2021 :-)
Have a nice day! ;)
I will solve your system by substitution.<span><span><span><span>2x</span>+<span>3y</span></span>=2</span>;<span><span>x+<span>6y</span></span>=<span>4x</span></span></span>Step: Solve<span><span><span>2x</span>+<span>3y</span></span>=2</span>for x:<span><span><span><span>2x</span>+<span>3y</span></span>+<span>−<span>3y</span></span></span>=<span>2+<span>−<span>3y</span></span></span></span>(Add -3y to both sides)<span><span>2x</span>=<span><span>−<span>3y</span></span>+2</span></span><span><span><span>2x</span>2</span>=<span><span><span>−<span>3y</span></span>+2</span>2</span></span>(Divide both sides by 2)<span>x=<span><span><span><span>−3</span>2</span>y</span>+1</span></span>Step: Substitute<span><span><span><span>−3</span>2</span>y</span>+1</span>forxin<span><span><span>x+<span>6y</span></span>=<span>4x</span></span>:</span><span><span>x+<span>6y</span></span>=<span>4x</span></span><span><span><span><span><span><span>−3</span>2</span>y</span>+1</span>+<span>6y</span></span>=<span>4<span>(<span><span><span><span>−3</span>2</span>y</span>+1</span>)</span></span></span><span><span><span><span>92</span>y</span>+1</span>=<span><span>−<span>6y</span></span>+4</span></span>(Simplify both sides of the equation)<span><span><span><span><span>92</span>y</span>+1</span>+<span>6y</span></span>=<span><span><span>−<span>6y</span></span>+4</span>+<span>6y</span></span></span>(Add 6y to both sides)<span><span><span><span>212</span>y</span>+1</span>=4</span><span><span><span><span><span>212</span>y</span>+1</span>+<span>−1</span></span>=<span>4+<span>−1</span></span></span>(Add -1 to both sides)<span><span><span>212</span>y</span>=3</span><span><span><span><span>212</span>y</span><span>212</span></span>=<span>3<span>212</span></span></span>(Divide both sides by 21/2)<span>y=<span>27</span></span>Step: Substitute<span>27</span>foryin<span><span>x=<span><span><span><span>−3</span>2</span>y</span>+1</span></span>:</span><span>x=<span><span><span><span>−3</span>2</span>y</span>+1</span></span><span>x=<span><span><span><span>−3</span>2</span><span>(<span>27</span>)</span></span>+1</span></span><span>x=<span>47</span></span>(Simplify both sides of the equation)Answer:<span><span>x=<span><span><span>4/7</span><span> and </span></span>y</span></span>=<span>2/<span>7
is what i got sorry if it don't help</span></span></span>
Only numbers possible would be five and zero